1980
DOI: 10.3758/bf03199898
|View full text |Cite
|
Sign up to set email alerts
|

Transient stimulation does not aid visual search: Implications for the role of saccades

Abstract: Previous demonstrations that performance on visual search tasks with briefly flashed presentations declines over time after the initial onset imply that saccades might be necessary for efficient acquisition of visual information. We imposed an additional abrupt onset and a displacement on character arrays containing letters and one numeral while subjects searched for the numeral. Presentations were always followed by a visual noise field. Presentation time varied (50-800 msec). We found that performance with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1

Year Published

1980
1980
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
(22 reference statements)
4
19
1
Order By: Relevance
“…8 Notably, Bundesen (1990), Kowler and Sperling (1980), Loftus and Kallman (1979), Massaro (1970), Rumelhart (1969), and Townsend (1981). 9 In previous formulations of the model, this a(t) function was defined somewhat arbitrarily-that is, on the basis of intuitionrather than generated on the basis of fundamental principles.…”
Section: The Stimulus Input Function Engenders the Sensoryresponse Fumentioning
confidence: 99%
“…8 Notably, Bundesen (1990), Kowler and Sperling (1980), Loftus and Kallman (1979), Massaro (1970), Rumelhart (1969), and Townsend (1981). 9 In previous formulations of the model, this a(t) function was defined somewhat arbitrarily-that is, on the basis of intuitionrather than generated on the basis of fundamental principles.…”
Section: The Stimulus Input Function Engenders the Sensoryresponse Fumentioning
confidence: 99%
“…Unlike, say, a simple threshold-detection task, digit recall is complex enough to require the fundamental processes enumerated above. At the same time, the task involves a stimulus that should not exceed short-term memory capacity and thus does not require assumptions about subjects' strategies about what to transfer to short-term memory (see, e.g., Rundus, 1971); involves a stimulus that is immediately masked, so that it does not require assumptions about iconic decay (see, e.g., Averbach & Sperling, 1961); involves items of relatively homogeneous difficulty, so that it does not require corrections for averaging artifacts (see, e.g., Kowler & Sperling, 1980); and does not involve partial report, so that it does not require assumptions about probe detection and utilization (see, e.g., Sperling, 1960).…”
Section: Digit-recall Taskmentioning
confidence: 99%
“…Correspondence should be addressed to G. R. Loftus, Department of Psychology, University of Washington, Seattle, WA 98195 (e-mail: gloftus@u.washington.edu). Kowler & Sperling, 1980;Loftus & Kallman, 1979;Massaro, 1970;Rumelhart, 1970;Shibuya & Bundesen 1988;Townsend, 1981). By what we will refer to as the basic random-sampling model, a stimulus is composed of a set of relatively homogeneous features.…”
mentioning
confidence: 99%
“…To examine the effect of abrupt onsets on visual information acquisition, we compared performance in the visual search task we had used earlier (Kowler & Sperling, 1980) for displays with gradual and with…”
Section: The Rationale For the Experimentsmentioning
confidence: 99%
“…In a previous paper (Kowler & Sperling, 1980), we found that visual search for a single-numeral target, embedded in an array of letters, was not aided by abrupt onsets. This conclusion was supported by three main results: (1) Visual search with displays containing two abrupt onsets (two brief flashes) was not better than visual search with displays containing a single abrupt onset (one long flash); (2) an abrupt onset created by imposing a rapid, lateral displacement on the stimulus was not useful-visual search with stationary displays was as good as visual search with displays containing a rapid displacement; and (3) visual search was consistent with a model in which information was acquired at a constant rate throughout a stimulus presentation.…”
mentioning
confidence: 99%